THE THREE FACTORS BEHIND THE ONLINE MULTILINGUAL IDENTITIES OF INDONESIAN EFL LEARNERS ON INSTAGRAM - Sibuea, Todo F. B.; Sekartaji, Maya; Butar butar, Erni J. (English Community Journal, 2023)
Social Networking Sites (SNS) are big part of the life of Indonesians because it provides diverse virtual communities for Indonesians to consume and exchange information. The presence of Indonesian communities and global audiences in the virtual networks creates the need for Indonesians to employ various linguistic repertoires in order to join the conversations in the SNS. The present study aims at discovering the components that shaped the multilingual identities that six Indonesian urban university students project on Instagram using their multilingual repertoires. Using a combination of multimodal analysis of the students’ posts on SNS and a semi-structured interview, this qualitative study reveals that academic background, online activities, and audience’s expectations are the factors that contributed to the construction of the students’ online identities. Hence, this paper calls for more similar studies about the multilingual identity construction of Indonesian EFL learners on SNS in the future.